Food acceptability and selection by astronauts on International Space Station missions informs strategies and risks for deep space exploration - Douglas, Grace L.; Bell, Suzanne T.; Roma, Peter G.; Oswald, Thomas; Young, Millennia (Frontiers in Psychology, 2025)
Characterization of the relationship between food system acceptability and repeat consumption within the spaceflight food system may be linked to caloric intake but the impact of food acceptability and repeat consumption has not been previously systematically investigated. In this study, 15 astronauts on the International Space Station (ISS) reported acceptability of the items in one meal a week over approximately 6-month and 1-year missions. The results indicated that acceptability scores did not decrease over the mission. Astronauts limited selections to their personal favorites early in the mission and did not consume foods they did not like. Although they continued to like the foods they chose, many foods were not rated by more than one individual, supporting variability in personal preference. Intake of only liked foods from mission start may impact total variety and quantity available to each astronaut within the restricted system on ISS, which may ultimately impact total nutritional intake. It also increases the challenge for exploration missions, where food may be pre-positioned and personal preferences may not be accommodated. Astronaut comments indicated specific food types and strategies that may help improve food system acceptability for future missions.